Pharmacokinetic changes of antibiotic, antiviral, antituberculosis and antifungal agents during extracorporeal membrane oxygenation in critically ill adult patients. (25th September 2017) - Hahn, J.; Choi, J. H.; Chang, M. J.
Summary: What is known and objective: Extracorporeal membrane oxygenation (ECMO) is a life‐saving system used for critically ill patients with cardiac and/or respiratory failure. The pharmacokinetics (PK) of drugs can change in patients undergoing ECMO, which can result in therapeutic failure or drug toxicity requiring further management of drug complications. In this review, we discussed changes in the PK of antibiotic, antiviral, antituberculosis and antifungal agents administered to adult patients on ECMO. These drugs are crucial for managing infections, which commonly occur during ECMO. Methods: A literature search was conducted using the PubMed and EMBASE databases with the following keywords: "extracorporeal membrane oxygenation OR extracorporeal membrane oxygenations OR ECMO" and "PK OR pharmacokinetics OR pharmacokinetic*" and "anti infective* OR antibiotic* OR antiviral* OR antituberculosis OR antifungal*." Results and discussion: Generally, the volume of distribution (Vd) increases and drug clearance (CL) and elimination decrease during ECMO. Highly significant changes in drug PK can occur by interactions with the ECMO device itself, drug characteristics, pathological changes and patient characteristics. This may affect the blood concentrations of drugs, which influence the success of therapy. The PK of vancomycin, piperacillin‐tazobactam, meropenem, azithromycin, amikacin and caspofungin did not change significantly in adult patients receiving ECMO. However, there were significant changes in the PK of imipenem, oseltamivir, rifampicin and voriconazole. The trough concentrations of imipenem were highly variable; oseltamivir had a decreased CL and increased Vd, and rifampicin concentrations were below therapeutic levels, even when a higher‐than‐standard dose was used in patients treated with ECMO. Additionally, voriconazole exhibited high mean peak concentrations during ECMO. What is new and conclusion: The impact of ECMO on PK varies among drugs in adult patients, and there is no consistent correlation between the effects observed in adult and infant studies. This review suggested that doses of imipenem, oseltamivir, rifampicin and voriconazole should be adjusted and therapeutic drug monitoring is needed when ECMO is used in adult patients. In the future, large PK trials in adults on ECMO are needed to provide optimal dosing guidelines. A PK/PD modelling approach will be useful for determining the precise impact of ECMO and other factors that contribute to PK changes for each drug. Finally, it is important to develop dosing guidelines based on PK/PD modelling studies that can be used in clinical practice.